INTENSIFIKASI PENGGUNAAN MEDIA SOSIAL UNTUK MEWUJUDKAN PERPUSTAKAAN MODERN DI ERA DIGITAL - Amaliah, Eni; SUmarno, Sumarno (UIN Raden Intan Lampung, 2021)
A library is a room or building that is used to store a collection of books or other collections of objects for visitors to read, borrow and refer to as reference material. On the other hand, the development of science and technology (IPTEK) affects all aspects of human life, including how to find information. The library as an institution as a source of public information must adapt to the development of science and technology, one of which is social media. The increasingly massive use of the internet has even reducedinterest in reading, so that the application of technology in the library household is a must..